2022
DOI: 10.1111/nph.17950
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of soil algae to the global carbon cycle

Abstract: Summary Soil photoautotrophic prokaryotes and micro‐eukaryotes – known as soil algae – are, together with heterotrophic microorganisms, a constitutive part of the microbiome in surface soils. Similar to plants, they fix atmospheric carbon (C) through photosynthesis for their own growth, yet their contribution to global and regional biogeochemical C cycling still remains quantitatively elusive. Here, we compiled an extensive dataset on soil algae to generate a better understanding of their distribution across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…While these photosynthetic microbes have key ecological and biogeochemical roles [ 10 13 ], they are thought to make a minor contribution to terrestrial primary productivity, compared to plants (but see refs. [ 14 , 15 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these photosynthetic microbes have key ecological and biogeochemical roles [ 10 13 ], they are thought to make a minor contribution to terrestrial primary productivity, compared to plants (but see refs. [ 14 , 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that photosynthetic microbes occur in a variety of terrestrial habitats, including sub-surface soils [ 15 17 ], exposed rocks [ 18 ], and bryophytes [ 19 ]. They encompass myriads of life forms and styles, with Cyanobacteria and Chlorophyta being the most commonly reported phyla in DNA-based global diversity surveys [ 2 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sargassum and other biomass-rich species in the oceans has been entertained-again not without polemic-for capturing large amounts of atmospheric CO 2 [42] avoiding the problem of land occupation and forest fires. 3 In either case, the potential of plants and algae (including soil-bound types [43]) could be further increased by engineering specific species for a superior CO 2 fixation job [44]. Possibilities include not just enhancing the efficacy of the utterly suboptimal RuBisCo [33,45,46], but also by increasing the electron flow through the Calvin Cycle [47], improving CO 2 internment [48,49], interfacing biological and abiotic systems [50], engineering overproduction of lignocellulosic materials, suberin and other recalcitrant polymers, e.g.…”
Section: The Players Of Global Carbon Balancementioning
confidence: 99%
“…Indeed, changes in landscape structure are likely to modify assembly processes, thereby impacting the composition, functionality and resilience of soil protist communities (Saleem et al, 2019). As soil protists are key players in soil food webs (Xiong et al, 2018), these changes can potentially have a cascading impact on ecosystem functioning and services such as fertility as well as carbon sequestration and storage (Jassey et al, 2022). It is thus likely that the ongoing agricultural abandonment and urbanisation in the Alps (Vannier et al, 2016) will lead to local and regional decreases in protist diversity in meadow soils with potentially important consequences for the functioning of these ecosystems.…”
Section: Landscape Structure Modulates the Rate Of Distance-decay In ...mentioning
confidence: 99%